Solarisation – An effective low cost substrate sterilization technique for the cultivation of milky mushroom (Calocybe indica) - G, Heera; M, Suharban; D, Geetha (Mushroom Research, 2020)
The increasing crop production is generating huge amount of agricultural waste creating serious environmental pollution and hazards. The agro wastes composed of lignin are the recalcitrant fractions which pose serious threat to nature. Utilization and recycling of agro waste in mushroom cultivation is one the eco-friendly profitable venture. In this context a study was conducted to evaluate the biological efficiency of milky mushroom production by utilising agro wastes as substrates subjected to different sterilisation procedures. The substrates used were paddy straw, spent mushroom substrate (SMS), and coir pith subjected to sterilization procedures viz., boiling, solarisation and chemical method. Solarisation of substrates SMS and paddy straw gave better mycelial growth and took minimum period for spawn run, initial production and harvest. SMS gave more number of sporophores and yield when compared to paddy straw and coir pith. Solarisation was the best sterilisation procedure for obtaining higher yield of milky mushroom. The coir pith substrate subjected to solarisation and boiling showed heavy incidence of contaminants viz., Trichoderma and Coprinus. The solarised SMS was the best substrate and sterilisation combination in producing higher yield of milky mushroom.